2021
DOI: 10.1088/1741-4326/ac35f9
|View full text |Cite
|
Sign up to set email alerts
|

The geometry of the ICRF-induced wave–SOL interaction. A multi-machine experimental review in view of the ITER operation

Abstract: As part of ITPA-Integrated Operational Scenario activities, this contribution reviews recent experimental characterizations of radio-frequency (RF)-induced scrape-off layer (SOL) modifications of various tokamaks worldwide and of the LArge Plasma Device at UCLA. The phenomenology, as observed using a large variety of measurement techniques, is consistent with expectations from RF sheath rectification. Emphasis is then put on the complex three-dimensional (3D) spatial patterns of the RF–SOL interaction, in rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 99 publications
1
15
0
1
Order By: Relevance
“…It has to be noted that the five antennas are equipped with W coated side limiters. Interestingly, the fraction of radiated power is very similar when operating LHCD or ICRH, despite ion acceleration in front of the ICRH antennas favouring W sputtering [29]. Discharges lasting more than 30 s were routinely carried out with LHCD alone using the actively cooled upper divertor and a discharge duration close to 1 min was obtained with 3 MW of LHCD (figure 9) [30].…”
Section: Rf Heated Plasmas and W Contaminationmentioning
confidence: 99%
“…It has to be noted that the five antennas are equipped with W coated side limiters. Interestingly, the fraction of radiated power is very similar when operating LHCD or ICRH, despite ion acceleration in front of the ICRH antennas favouring W sputtering [29]. Discharges lasting more than 30 s were routinely carried out with LHCD alone using the actively cooled upper divertor and a discharge duration close to 1 min was obtained with 3 MW of LHCD (figure 9) [30].…”
Section: Rf Heated Plasmas and W Contaminationmentioning
confidence: 99%
“…The RF waves launched by the antenna cause sheath rectification [18,32]. An enhanced DC potential develops on the plasma-facing components on which the RF waves are incident (usually the antenna surface itself, but in NSTX we must consider the possibility that this happens on the divertor), which causes a DC current to flow mostly along the field lines, the direction along which the magnetized plasma conducts current most easily.…”
Section: Direct Currents Along Field Linesmentioning
confidence: 99%
“…usually from the active ICRF antenna to the divertor [38]. Perkins deduced the direction of the DC currents from the sign of the floating potential on Langmuir probes, and found that DC currents in NSTX flow in the opposite direction [32], as if the current is mainly driven by divertor sheath rectification.…”
Section: Direct Currents Along Field Linesmentioning
confidence: 99%
“…As the toroidal phase decreases from dipole (Δφ = 180 • ) to 80 • , the brightness on the right limiter increased by a factor 1.5. Although the coupled power decreases by a factor of 2 as the antenna departs from its matching point, applying a factor √ P ICRF (homogeneous to the antenna electric fields which are a proxy to RF sheath amplitudes [43]) to compensate for lower RF power leads to a normalized brightness increases by around 1.8.…”
Section: Radiated Power and Impurity Productionmentioning
confidence: 99%